26. GAMBARAN HISTOPATOLOGIS GINJAL TIKUS PUTIH (Rattus novergicus) JANTAN YANG DIINFEKSIKAN Trypanosoma evansi DAN DIBERI EKSTRAK DAUN SERNAI (Wedelia biflora) (Histopathology of Male Rat (Rattus novergicus) Kidney Infected with Trypanosoma evansi and Treated with Sernai Leaves Extract (Wedelia biflora)) - Yudha Fahrimal; Rahmiwati R; Dwinna Aliza (Universitas Syiah Kuala, 2016)
This research was aimed to study histopathology of rat kidney infected with Trypanosoma evansi after administration of sernai leaves extract (Wedelia bifolora). The samples used were kidneys of 25 male rats strain Wistar which were equally divided into 5 treatment groups. Group P1 was uninfected and untreated control, group P2 was infected with 1x103 T. evansi but not sernai leaves extract, rats from groups P3, P4, and P5 were infected with 1x103 T. evansi and given sernai leaves extract with the dose of 30 mg/kg bw, 45 mg/kg bw, and 60 mg/kg bw respectively. The sernai extract was administered orally using a stomach tube for 3 consecutive days. The next day after last treatment, all rats were sacrificed and necropsied. Kidneys were collected for histopathological examination such as degeneration and necrosis of tubules cells, convoluted contortus duct lumen, and adhesion and atrophy of glomerulus. Sernai leaves extract with the dose of 45 mg/kg bw was the most effective dose to prevent kidney damage due to T. evansi infection.